EFEKTIVITAS PENGELOLAAN DANA KEISTIMEWAAN DIY: ANTARA ALOKASI, PENYERAPAN ANGGARAN DAN REALITAS SOSIAL - Lingga Yudhana (An Nuqud Journal of Islamic Economics, 2026)
This study aims to analyze the management of the Special Region Fund (Dais) in the Special Region of Yogyakarta (DIY), covering allocation trends, budget absorption realization, and implementation challenges. The research method employed is descriptive with a qualitative approach through secondary data analysis for the 2013-2022 period. The results indicate that the Dais allocation has increased significantly, reaching IDR 1.32 trillion in 2022, with a highly effective absorption rate (above 90% since 2016). Cultural affairs remain the top priority, accounting for 62.58% of the total allocation. Nevertheless, the utilization of Dais still faces social reality challenges, such as the poverty rate in DIY remaining above the national average and limited budget flexibility to address urgent issues like waste management due to regulatory constraints. This study suggests the need for specific local regulations (Raperda) to expand the reach of Dais benefits for more equitable community welfare